Financial Performance of Sugarcane Cooperatives in East Java - Ening Ariningsih (Analisis Kebijakan Pertanian, 2014)
East Java is the largest sugarcane producing center in Indonesia where cooperatives have an important role on sugarcane agribusiness. This study aimed to analyze the financial performance of sugarcane cooperatives in East Java. Financial ratios related to profitability, liquidity and solvency coupled with a set of panel data over the period 2008-2011 were used in this study. The results of the study indicated that the majority of sugarcane cooperatives in East Java, both KPTRs and KUDs, had a relatively low profitability, and were liquid but not solvent. However, the existence of some sugarcane cooperatives in East Java that had relatively a high net surplus indicated a good sign on their development. Based on the results of this study, the suggestion to improve further implementation strategies of sugarcane cooperatives in East Java are as follows: (1) improvement of cooperative management and implementation of cooperative principles, (2) significant differentiation of services upon cooperative membership, (3) strengthening the members’ capital share, and (4) government support in terms of facility and subsidy as well as supporting their autonomy.